Impact of Covid 19 Confirmed Cases, Covid 19 Confirmed Death Cases and Financial Performance on Cumulative Abnormal Return (CAR) - Restu Agusti; Pipin Kurnia; Edfan Darlis; Mudrika Alamsyah (Integrated Journal of Business and Economics (IJBE), 2021)
This study aims to see the effect of the variable positive confirmed cases of covid 19, confirmed death cases of covid 19, return on assets (ROA), leverage, liquidity and company size (size) on cumulative abnormal returns (CAR) during the Covid 19 pandemic. Samples used in this research is purposive sampling. This research was conducted on LQ45 companies listed on the IDX in 2020 during the COVID 19 pandemic. The results of hypothesis testing in this study showed that Positive confirmed cases of Covid 19, Cases of death confirmed positive for Covid 19, Return on assets (ROA) and Company Size (Size) shows no effect on CAR but Leverage (DER) and Liquidity (CR) shows there are an effect on CAR.